Faktor-Faktor Penerimaan Aplikasi Mobile Rumah Sakit Bhayangkara Surabaya Dengan Metode TAM - Bagaskara Antaris; Asif Faroqi; Anita Wulansari (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The queue application at Bhayangkara Hospital Surabaya is a mobile-based application designed to facilitate patients in registering for appointments at the hospital. Data was obtained through a survey conducted among application users and analyzed using multiple linear regression with the assistance of SPSS Version 26. The objective of this research is to determine the factors that influence the acceptance of the mobile application by users or patients of Bhayangkara Hospital Surabaya based on the Technology Acceptance Model (TAM) framework. Thus, this study conducted an acceptance analysis by identifying the factors that affect the acceptance of the Mobile Application of Bhayangkara Hospital Surabaya. The method used in this research is the Technology Acceptance Model (TAM) using six main variables: Complexity, Voluntariness, Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Behavioral Intention to Use, and Actual Use. The chosen technique for this research is simple random sampling. The sample size taken was 380 respondents from a population of 4935 users. Based on the results of the data analysis conducted, it can be concluded that out of the ten hypotheses in this study, the voluntariness variable does not have an effect. Therefore, complexity, perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to use an information system are factors that influence users to continue using the system